2011
DOI: 10.1016/j.ultsonch.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced decomposition of reactive blue 19 dye in ultrasound assisted electrochemical reactor

Abstract: Textile industry effluents contain reactive dyes that may harm our receiving waters. A typical reactive blue (RB) 19 dye is frequently detected in significant concentrations in textile industry effluents. Such dyes have generally shown resistance to decomposition and tend to persist in the environment for long periods and multiply the impacts to water and environment. Therefore, the present investigation focused on high-rate decomposition of a typical reactive dye RB 19 under various ultrasound and electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…In the former, the catalyst couple merely plays the role of an electron carrier (mediator), whereas the transitory formation of catalyst-substrate adduct occurs in the latter [25]. In addition, the electrons may then react with species adsorbed on the surface, yielding radicals such as O 2 -as a result of the presence of hydroxyl groups, water, and oxygen at the surface of the Gd 3? , Nd 3?…”
Section: Mineralization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former, the catalyst couple merely plays the role of an electron carrier (mediator), whereas the transitory formation of catalyst-substrate adduct occurs in the latter [25]. In addition, the electrons may then react with species adsorbed on the surface, yielding radicals such as O 2 -as a result of the presence of hydroxyl groups, water, and oxygen at the surface of the Gd 3? , Nd 3?…”
Section: Mineralization Studiesmentioning
confidence: 99%
“…Reactive dyes are extensively used in the textile industry due to the presence of reactive groups in their molecules which bind to fibers through covalent bonds. The main problem associated with the use of reactive dyes is their low affinity for fabrics resulting in relatively high dye concentrations in textile wastewater [2]. Reactive dyes exhibit a wide range of different chemical structures, primarily based on substituted aromatic and heterocyclic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Lissamine Green B [10], Trupocor Red [10], Reactive Black 5 [10], Acid Black [10], Methyl Orange [10][11][12], Rhodamine B [12], Methylene Blue [12], Reactive Brilliant X-3B [12], and Reactive Blue 19 [13] have been used as reactive dyes for acoustic cavitation coupled with electrochemical treatment. Hydrodynamic cavitation has also been used to enhance the electrochemical treatment of Brilliant Red X-3B [9].…”
Section: Sonoelectrochemical Degradation Of Textile Dyesmentioning
confidence: 99%
“…Hydrodynamic cavitation has also been used to enhance the electrochemical treatment of Brilliant Red X-3B [9]. For all these studies, various electrode materials (Ti-IrO 2 [9], graphite [10], platinum [12], PbO 2 [13]) and three-dimensional electrodes [11] were employed and the effect of several parameters were studied, including the ultrasonic power/intensity, the cell design, pH, initial dye concentrations, and so on. It was observed that pseudo-first-order kinetics were obtained in most cases where di-azo dyes showed slow degradation rates compared with mono-azo dyes [10].…”
Section: Sonoelectrochemical Degradation Of Textile Dyesmentioning
confidence: 99%
“…Recently, Siddique et al (2011) reported the decomposition of un-hydrolyzed and hydrolyzed forms of reactive blue (RB) 19 dye by ultrasound assisted electrochemical process using lead oxide as working electrode. The experiments were conducted at various pH values in the range of 3-9 and various ultrasonic frequencies (20-80 kHz) using 50 mg L -1 dye concentration for 120 min.…”
Section: Ultrasound In Electrochemical Degradation Of Pollutants 217mentioning
confidence: 99%